Etika Profesi Akuntan dalam Perspektif Ideologi pancasila - Ade Ikhlas Amal Alam (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2021)
The purpose of this paper is to determine the ethics of the accounting profession in the perspective of the Pancasila ideology. The approach taken in this paper uses descriptive qualitative. The result of this paper is that an accountant at work must always uphold the five principles of this country are divinity, humanity, upholding unity, deliberation, and justice so that the accountant's code of ethics is still upheld and closes fraudulent actions that harm many people.